Redesign of Bus Services Using Quality Function Deployment (QFD) to Improve Services to Passenger (Case Study: PO XYZ) - Denny Nurkertamanda; Fakhril Husain; Yusuf Widharto (OPSI, 2021)
For products in the form of services, customer satisfaction is the most important thing because consumers see services from what other consumers say. As with the PO XYZ also use service which relies on passenger satisfaction. PO XYZ have an experience in reduced consumer satisfaction and with the competitor rise the passenger turn to another competitor. Because of this, it is necessary to conduct this research, for winning customer PO XYZ heart by listening passenger desires. This research used Quality Function Deployment (QFD) which only reached the second phase. Data collection through open passenger questionnaires. In the first phase, product planning, it was found that cleanliness of the bus was a major factor that had to be addressed by PO XYZ of 9.477%. The first phase output in the form of technical characteristics becomes the second phase input, namely design planning. In the second phase four suitable service design alternatives were made. Of the four design alternatives, a third service design is obtained which is the choice with a value of 4.74 from scale 6. This shows that the third alternative service should be implemented as an effort to improve quality in meeting passenger satisfaction of PO XYZ.